The influence of unconventional monetary policy tools: an euro area perspective - Pečiulis, Tomas; Vasiliauskaitė, Asta (Business, Management and Economics Engineering, 2024)
Purpose – This article aims to investigate the influence of unconventional monetary policy tools (UMPTs) employed by the European Central Bank (ECB) on the inflation rate and GDP growth rate within the euro area, motivated by the principles of the Taylor rule.Research methodology – Elastic net regression with ARIMA residuals was used to analyse the relationship between UMPTs and economic indicators, measured by adjusted R-squared. Six samples were constructed, and hypothesis testing was performed using moving block bootstrapping. Residual diagnostics were used for model validation.Findings – The study revealed significant impacts of UMPTs, particularly in combination with interest rates, on inflation rates. However, adjusted R-square values for GDP growth rate were less pronounced, indicating a more complex relationship. Research contributes to understanding the dynamics of monetary policy transmission mechanisms, informing policy institutions, and guiding future research directions.Research limitations – Limitations include the focus on the euro area and the absence of analysis in other major economies. Future research should address these limitations and incorporate additional variables for a more comprehensive analysis.Practical implications – The findings provide insight for policymakers regarding the efficacy of UMPTs in influencing inflation rates, aiding in informed decision-making in monetary policy formulation and implementation.Originality/Value – This study contributes novelty by comprehensively analysing the relationship between UMPTs and economic indicators within the euro area, providing valuable insight into monetary policy institutions, and guiding future research directions.